Development of Structural Materials and House Construction in Merauke - Anton Topan,; Biatma Syanjayanta,; Saliki,; Maichel S. Wijaya Mita,; Aldi M. Amar Makruf, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The purpose of this research is to find out what factors have resulted in people's interest changing to be interested in the minimalist house model. This will be associated with several determining factors seen from the structural factors in the old building compared to the building model that is widely built by the Merauke Community. The structure of the Kancingan house for the people of Merauke consists of the wooden structure of this historical building. Along with the times, there has been a change in function from the aspect of building construction which was once considered a strong structure. This can be influenced by the cost, materials, culture and the level of difficulty in building. The author identifies through a case study of kancingan houses around the city of Merauke which includes a residential area where almost 70% of the houses have a kancingan structure. The result of this identification is to find out what causes people to prefer modern houses over kancingan houses.